Effects of Lifestyle Modifications on Elevated Blood Pressure and Excess Weight in a Population of Italian Children and Adolescents. (4th July 2018) - Genovesi, Simonetta; Orlando, Antonina; Rebora, Paola; Giussani, Marco; Antolini, Laura; Nava, Elisa; Parati, Gianfranco; Valsecchi, Maria Grazia
Abstract: BACKGROUND: Children's excess weight is a common problem due to low-quality diet and poor physical activity and is a risk factor associated with hypertension. Aim of this study was to assess the effect of a nonpharmacological multidisciplinary intervention on blood pressure (BP) and body weight in a population of children with excess weight and/or elevated BP. METHODS: Children consecutively referred to a Prevention of Cardiovascular Risk Clinic by the primary care pediatrician from 2009 to 2015 were assessed at baseline and followed up over time. RESULTS: Out of 273 children (median age 11.4 years, 55% male), 61% were excess weight only, 7% had elevated BP only, and 32% showed both conditions. The probability of reaching the clinical target (normal weight and BP values) at 1 year of follow-up was 19% (confidence interval [CI]: 14%; 24%) and increased up to 38% (CI: 28%; 47%) at 3 years. At 1 year of follow-up, in the overall population both body mass index (BMI) and systolic BP z -scores decreased significantly from 1.77 to 1.47 and from 0.99 to 0.52, respectively ( P < 0.0001). BP was significantly reduced in both children with elevated BP only (reduction = 0.91, P = 0.0157) and subjects with excess weight and elevated BP (reduction = 0.89, P < 0.0001). Variables significantly related with systolic BP z -score at 1 year of follow-up were baseline systolic BP z -score and BMI z -score reduction during follow-up ( P < 0.001 and P = 0.0003, respectively). CONCLUSION: Our data demonstrate the efficacy of lifestyles modification on weight and BP in children, both when elevated BP and excess weight were present as distinct clinical problems and in the case of their association.